PENERAPAN PRINSIP PARTICIPATRORY LEARNING AND ACTION UNTUK MEMBERDAYAKAN MASYARAKAT KELOMPOK WANITA TANI MELATI DI KELURAHAN KALEBAJENG KECAMATAN BAJENG KABUPATEN GOWA - Mukhlisah, Anny Nurul; Kartini, Marzuki; Muhammad, Asri (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research aims to determine the application of the principles of participatory learning and action to empower the community in women farming groups in Kalebajeng Village, Bajeng District, Gowa Regency. This type of research is descriptive research using qualitative methods, data collection using observation, interview and documentation techniques. The subjects in this research were 6 people, namely, the head of the women's farmer group, 1 assistant (tutor) and 4 members. Based on the results of the research that has been carried out, it can be concluded that there are five principles in applying the principles of Participatory Learning and Action to empower the community in women farming groups. (1) group learning has been implemented with the formation of study groups and there are no special requirements to become members (2) Multi Perspective has been implemented but not yet completely, women farmers have knowledge of planting and seeding and are not taught how to process the harvest. (3) Specific location, located in the yard of the chairman's house with quite large land, available water source (4) Facilitation has been realized, facilities and infrastructure are not yet optimally fulfilled, there are stakeholders who help buy or find partners to sell the harvest. (5) The leader of change is to improve the economy, increase the skills or skills of kwt members.